Molecular Insights into the Therapeutic Potential of Curcuma amada Rhizome: A Network Pharmacology and Docking Approach - Fatriani, Rizka; Istiadi, Khaerunissa Anbar; Khairani, Iffa Afiqa (Tropical Biopharmaca Research Center, IPB University, 2025)
The rhizome of Curcuma amada (ginger mango) has traditionally been used for various medicinal purposes. However, its molecular targets and mechanisms of action are still poorly understood. This study aimed to predict the potential bioactive compounds and target proteins of C. amada using network pharmacology and molecular docking approaches. A total of 110 compounds were identified, and their predicted targets were analyzed through a protein-protein interaction (PPI) network, enrichment, and disease analysis. Key targets include phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha isoform (PIK3CA) and tyrosine-protein kinase JAK2 (JAK2), both of which are closely related to cancer-related pathways. Four compounds, β-eudesmol, (E,Z)-farnesol, spathulenol, and τ-muurolol, were selected for molecular docking studies. Validation of the docking protocol through re-docking showed low RMSD values ​​(0.667 Å for PIK3CA and 0.474 Å for JAK2), confirming the reliability of the method. The docking results demonstrated that the native ligands and selected compounds formed multiple hydrogen bonds and extensive hydrophobic interactions with key residues in the active site. Notably, most of the interactions were hydrophobic, which is consistent with the volatile nature of the ligands. The binding affinity was below –5 kcal/mol for all tested compounds. These findings suggest that C. amada rhizomes contain bioactive compounds capable of modulating cancer-related targets, thus providing a molecular basis for their potential therapeutic effects.